Negotiating The Indian “Problem” - Dyck, Noel (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1986)
This essay examines the formulation of the so-called Indian “problem” as a significant element in relations between Indians and non-Indians in Western Canada. Making use of the concept of the culture of public problems, the author identifies some of the means by which Indian representatives seek to renegotiate with non-Indians a new understanding of the nature of the Indian “problem”.